Root canal microflora - George, Marina; Koberová Ivančaková, Romana (Acta Medica, 2007)
Modern day endodontics is undergoing a massive change with the introduction of new molecular based techniques for microbial identification. This review focuses on the microbiota in untreated and root-filled canals. It will also describe briefly the recent developments in microbial identification and the mechanisms by which certain species of microbes are able to invade and establish themselves in the root canal.
Keywords: klinické laboratorní techniky; Clinical Laboratory Techniques; Actinomyces; polymerázová řetězová reakce; Polymerase Chain Reaction; Bacterial Infections; lidé; zubní kořen; bakteriální infekce; Financing, Government; Mouth Mucosa; Tooth Root; molekulární biologie; financování vládou; ústní sliznice; Molecular Biology; Bacteria; Candida; Humans